KEEFEKTFAN MEDIA MOONSTAR PADA PEMBELAJARAN TEMA 2 KELAS IV - Ita Yuliana Suparjo; Supandi Supandi; Iin Purnamasari (FKIP, PGSD, Universitas Slamet Riyadi, 2019)
The aimed of the research was determined the effectiveness of Moonstar's media on learning themes always to save energy in grade IV of Elementary School in completing and improving learning outcomes. This type of research was quantitative research in the form of research Pre Experimental Design in the form of One Group Pretest-Posttest Design. The study population was fourth-grade students at SDN Tambakrejo 02 academic year 2018/2019. The study sample was 36 fourth grade students using non-probability sampling techniques. The research data was obtained through tests (pretest-posttest), observation, documentation, and interviews. The results of the pretest scores were obtained an average value of 52 and the average posttest score was 77. The increase in the value of the pretest and posttest was calculated using a gain test which was 0.5 including the medium category. Based on the t-test analysis it is known that t count is more than t table (36.255> 0.681) then H0 is rejected and Ha is accepted. Affective value of learning 1 obtained an average of 79.7 , while meeting 2 increased to 84.6. It can be concluded that the Moonstar media was effectived in the theme of Always Save Energy learning in Grade IV of Elementary School